The think aloud method: Some concerns addressed - Vijay Kumar (Journal of Modern Languages, 2017)
This paper will first discuss the theoretical underpinning of the Think Aloud Method. Secondly, it will relate the TA method to the working memory by considering writing as a problem solving activity. Finally, it will discuss some theoretical and methodological concerns of using this method and how these were addressed in a study.